Identifying Zimbabwean institutional investor's intentions to invest in ipps: evidence from the theory of planned behaviour - Ruwanika, Jonathan (Graduate School of Business (GSB), 2023)
There is a lack of capital to fund Zimbabwean energy infrastructure needs. An inability of Independent Power Producers (IPPs) that have obtained licenses to reach financial closure suggests a deficiency in Zimbabwe's long-term capital markets. This study proposes an innovative financing solution premised on Zimbabwean institutional investors. This study aims to examine the reasons for the lack of interest by institutional investors to invest in IPPs albeit appearing ideally suited to do so. The theory of planned behaviour was used as a theoretical framework to dissect factors that influence the intention to invest in IPPs and identify the determinants of the actual behaviour. Structural equation modelling was employed to analyse attitudes, subjective norms, and perceived behavioural control from a sample of 105 institutional investors in Zimbabwe. The findings suggests that attitude towards behaviour, subjective norms, and perceived behavioural control had a positive and significant influence on the intent by institutional investors to invest in IPPs in Zimbabwe. Perceived Behavioural Control had the most significant influence pointing to respondents' belief in Institutional investors' competency in investing in IPPs. Attitude Towards behaviour had the lowest influence meaning respondents were less confident in the fact that IPPs were good investments. However, there is a disconnect between the strong and positive intention to invest with the actual investment behaviour. The study concludes with an approach that the Zimbabwean government can take to address policy and provides recommendations for future research. This approach includes; mechanisms used to incentivize investment in energy infrastructure projects by local institutional investors, current tariff methodologies, and improving financial education about energy infrastructure as an asset class for local investors to improve investment attitudes